Medicare Beneficiaries Face Growing Out-Of-Pocket Burden For Specialty Drugs While In Catastrophic Coverage Phase - Trish, Erin (Health Aff (Millwood), 2016)
The Affordable Care Act (ACA) includes provisions to reduce Medicare beneficiaries’ out-of-pocket spending for prescription drugs by gradually closing the coverage gap between the initial coverage limit and the catastrophic coverage threshold (known as the “doughnut hole”) beginning in 2011. However, Medicare beneficiaries who take specialty pharmaceuticals might still face a large out-of-pocket burden because of uncapped cost sharing in the catastrophic coverage phase. Using 2008–12 pharmacy claims data from a 20 percent sample of Medicare beneficiaries, we analyzed trends in total spending and out-of-pocket spending among Medicare beneficiaries who take at least one high-cost specialty drug from the top eight specialty drug classes in terms of spending. Annual total drug spending per specialty drug user studied increased considerably during the study period, from $18,335 to $33,301, and the proportion of expenditures incurred while in the catastrophic coverage phase increased from 70 percent to 80 percent. We observed a 26 percent decrease in mean annual out-of-pocket expenditures incurred below the catastrophic coverage threshold, likely attributable to the ACA’s doughnut-hole cost-sharing reductions, but increases in mean annual out-of-pocket expenditures incurred while in the catastrophic coverage phase almost entirely offset these reductions. Policy makers should consider implementing limits on patients’ out-of-pocket burden.